FORMATION OF ANTI-CORRUPTION CHARACTER IN THE YOUNGER GENERATION BASED ON PANCASILA IDEOLOGY - ., Sugiyanto; Ramadhani, Rizky (JURNAL SETIA PANCASILA, 2024)
Corruption has become a serious issue in various layers of society and the state, posing a threat to morals, ethics, and sustainable development. To address this problem, efforts to instill anti-corruption character education are of utmost importance. The aim of this research is to analyze the ways to shape anti-corruption character among the younger generation based on the values embedded in Pancasila, so that the Indonesian youth can grow up as honest and anti-corruption individuals. The results of this study indicate that efforts can be made to cultivate anti-corruption character from an early age in children, starting even before they enter school, by teaching them about justice and not encroaching upon the rights of others. Furthermore, educational activities for students and university students can be employed to introduce anti-corruption character. Lastly, by advocating anti-corruption actions on social media, it will manifest a form of social sanction against wrongdoers and cultivate an anti-corruption attitude in the wider society.